MANAGEMENT OF ENTERPRISE DEVELOPMENT BASED ON COMPLEX TECHNOLOGY: STRATEGIC AND INNOVATIVE ASPECT (Development Service Industry Management, 2023)
In modern conditions, a significant share of enterprises whose business is actively developing are looking for new ways to increase efficiency and competitiveness.It was found that the advantages of technological management become the driving force of strategic changes, as well as the competitive advantage of business entities and their stakeholders. The purpose of the article is to study the strategic and innovative aspects of the process of managing the development of an enterprise based on complex technology in modern conditionsAn analysis of the relationship between the components of the enterprise development management system, formed on the basis of complex technology, was carried out. The key principles of ensuring effective implementation of complex technologies at all stages of enterprise development are: principles of rationality, optimization and systematicity.It is substantiated that when considering the innovative aspect of enterprise development management based on complex technology, attention should be focused on the implementation of innovative approaches and technologies to achieve strategic goals and increase competitiveness. From a strategic point of view, the same process should guide the management entity to define long-term goals and strategies that ensure the successful implementation of innovative approaches and technologies. It has been proven that in order to achieve high sustainable results in the enterprise development management system, a combination of both aspects should be ensured when planning and evaluating management technologies.It was determined that the implementation of information systems requires significant strategic changes in management practices, as well as high qualification of personnel. This means not only reviewing communication models and updating document management systems, but also full digitization of business processes.
Keywords: management; enterprise; management technologies; strategic changes; internal environment; external environment; competitive advantages; business process; complex technology